Correspondence testing studies - Dan-Olof Rooth (IZA World of Labor, 2014)
Anti-discrimination policies play an important role in public discussions. However, identifying discriminatory practices in the labor market is not an easy task. Correspondence testing provides a credible way to reveal discrimination in hiring and provide hard facts for policies. The method involves sending matched pairs of identical job applications to employers posting jobs—the only difference being a characteristic that signals membership to a group.
Keywords: D2; J1; J2; J7; 330; correspondence testing; taste-based discrimination; statistical discrimination